Contribution of cognitive factors to the prediction of post-traumatic stress disorder, phobia and depression after motor vehicle accidents. - Ehring, T; Ehlers, A; Glucksman, E (2006)
Past research into the psychological consequences of traumatic events has largely focused on post-traumatic stress disorder (PTSD), although other anxiety disorders and depression are also common in the aftermath of trauma. Little is known about differential predictors of these conditions. The present study investigated the extent to which theoretically derived cognitive variables predict PTSD, phobias and depression after motor vehicle accidents. The cognitive predictors were compared to a set of established, mainly non-cognitive predictors. In addition, we tested how disorder-specific the cognitive predictors are. Participants (n=101) were interviewed within a year after having been injured in a motor vehicle accident. Diagnoses of PTSD, travel phobias and depression, symptom severities and predictor variables were assessed with self-report questionnaires and structured interviews. In multiple regression analyses, the sets of cognitive variables derived from disorder-specific models explained significantly greater proportions of the variance of the symptom severities than the established predictors (PTSD 76% vs. 45%, depression 72% vs. 46% and phobia 66% vs. 40%), and than cognitive variables derived from the models of the other disorders. In addition, the majority of individual cognitive variables showed the expected pattern of differences between diagnostic groups. The results support the hypothesis that disorder-specific sets of cognitive factors contribute to the development and maintenance of PTSD, phobias and depression following traumatic events.